Rice bran replacement in clarias gariepinus fingerlings diets with pleurotus florida stalk - Hasniyati Muin; Nurul Nadwa Abdul Fatah; Mohd Hakimi Mohd Nor; Shaharudin Abdul Razak (Universiti Kebangsaan Malaysia, 2013)
The effect of replacement of ricebran by mushroom stalk (Pleurotus florida), an agriculture waste on growth performance of African catfish (Clarias gariepinus) fingerlings was investigated for 42 days. Three isonitrogenous (32% crude protein) experimental diets containing 100% (Diet 1), 50% (Diet 2) and 0% (Diet 3) mushroom meal were formulated. Each diet was randomly allocated to triplicate groups of fingerlings in experimental tanks, with each tank stocking 12 fishes. The fishes were fed twice daily to apparent satiation for 6 weeks. Good survival rates were obtained from fish fed with Diet 1 (94%) and Diet 3 (94%). There was no significant differences in body weight gain (BWG), specific growth rate (SGR) and feed conversion ratio (FCR) among all diets (p>0.05). The fish fed with Diet 1 showed the best BWG, SGR, FCR and PER compared with Diet 2 and Diet 3. An economic evaluation indicated that Diet 1 gave the lowest production cost at RM2.03/kg followed by Diet 2 and Diet 3 at RM2.18/kg and RM2.38/kg, respectively. This study showed that the best diet was Diet 1 with 100% replacement of rice bran with mushroom stalks costing RM2.03/kg, the cheapest among the three diets.